2020
DOI: 10.1038/s41598-020-67167-3
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ activity released from platelet-rich fibrin adsorbs to titanium surface and collagen membranes

Abstract: Platelet-rich fibrin (PRF) contains a broad spectrum of bioactive molecules that can trigger several cellular responses. However, these molecules along with their upstream responses remain mostly uninvestigated. By means of proteomics we revealed that PRF lysates contain more than 650 proteins, being TGF-β one of the few growth factors found. To uncover the major target genes regulated by PRF lysates, gingival fibroblasts were exposed to lysates obtained from PRF membranes followed by a whole genome array. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 58 publications
8
49
0
Order By: Relevance
“…Given the proposed functions of DCN and BGN, SLRPs may be involved in the control of TGF-β activity and collagen fibril formation in the peritoneum [ 24 ]. Our previous in vitro data support the binding capacity of collagen membranes for TGF-β [ 41 , 42 ]. Thus, the identification of various leucine rich proteins in both the membrane and the matrix reflects the composition of the original tissue and may translate into a biological activity in the biomaterial.…”
Section: Discussionsupporting
confidence: 76%
“…Given the proposed functions of DCN and BGN, SLRPs may be involved in the control of TGF-β activity and collagen fibril formation in the peritoneum [ 24 ]. Our previous in vitro data support the binding capacity of collagen membranes for TGF-β [ 41 , 42 ]. Thus, the identification of various leucine rich proteins in both the membrane and the matrix reflects the composition of the original tissue and may translate into a biological activity in the biomaterial.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, we determined whether blocking of the TGF-β receptor 1 kinase with SB431542 affects the expression of IL11. In support of the notion that IL11 is a highly sensitive TGF-β target gene [13][14][15] and even mediates the effects of TGF-β in vivo [16,17], SB431542 completely blocked the expression when activated with the supernatant but also the lysates of MG and CG2 ( Figure 5). Further support for the TGF-β activity in the supernatant of MG and CG2 comes from findings that the TGF-β neutralizing antibody reduced IL11 mRNA expression in two independent experiments from 19.0/18.3 to 3.2/1.4 (MG) and 2.0/28.3 to 0.7/0.9 (CG2).…”
Section: Tgf-β Receptor I Kinase Is Required To Increased Tgf-β Targesupporting
confidence: 61%
“…Moreover, and considering that the detection of TGF-β on the protein level not necessarily allows conclusions on the activity of the growth factor, we have performed a bioassay, refining previous observations to a functional level. This bioassay was used to report the TGF-β activity of bone conditioned medium [22], acid bone lysate [21], enamel matrix derivatives [14], and lysates of PRF membranes [13]. Surprisingly, TGF-β is not part of the proteomic signature of the MG membrane (Lee et al unpublished) with maybe attributed to the detection limit of the method; it thus seems that a bioassay with oral fibroblasts being highly sensitive to TGF-β signaling is an appropriate cellular tool to identify this growth factor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heating, however, not only inactivates plasminogen and coagulates albumin; it might also affect the activity of the catalase [21] and growth factors intrinsic to the PRF clot. We recently performed a proteomic analysis combined with a whole genome gene array of a traditional PRF membrane and identified that TGF-β was a major growth factor with respect to its activation of genes in oral fibroblasts [22]. TGF-β activity is identified by its ability to regulate respective target genes, most notably IL11 and NOX4, that appeared in multiple independent screening approaches involving enamel matrix proteins [23], bone conditioned medium [24] and acid bone lysates [25].…”
Section: Introductionmentioning
confidence: 99%